Asymmetric response to earnings news across different sentiment states: The role of cognitive dissonance - Li, Zhuo; Wen, Fenghua; Huang, Zhijian James (Journal of Corporate Finance, 2023)
Using the Chinese stock market data, we test the hypothesis that cognitive dissonance influences the stock market response to earnings news. Supporting this notion, we find that investors disregard earnings news that contradicts their sentiment due to cognitive dissonance, thereby causing a muted announcement date price reaction to such news. Further analysis shows that higher retail concentration and greater valuation uncertainty of the underlying firm exacerbate this cognitive dissonance and hence amplify its impact, but less credible financial report does not. Finally, we find that cognitive dissonance is temporary for bad news under optimism, but is quite persistent for good news under pessimism. Overall, our findings offer a behavioral bias explanation to understand why investors underuse accounting information.